Chemistry conditions and corrosion behaviour in simulated crevices of alloy steel. (19th May 2022) - Puspalata, R.; Chandran, Sinu; Veena, S.; Mohan, T. V. Krishna
ABSTRACT: Control and mitigating crevice corrosion demand a thorough understanding of the prevailing chemistry conditions inside the crevice. To match and predict the dynamics in chemistry conditions occurring inside a crevice appropriately, good crevice models necessitate extensive experimental data. This paper presents the accurate determination of the ionic species in the minute volume of crevice solution and redox potential measurements in fabricated simulated crevices of different dimensions/geometry in different stainless steel alloys. Crevice geometries fabricated from carbon steel (CS) 106 B and stainless steel (SS) 316 materials were exposed to varying water chemistry conditions in a static autoclave at high temperatures. The change in pH, conductivity, ionic concentrations, electrochemical potential and effectof corrosion inhibitors inside the crevice were monitored after exposure in an alkaline medium with and without chloride. Bulk solution pH showed a reduction in alkalinity, conductivity and enhancement in anion concentrations. About 58 times increase in Cl − was measured.